Do multiple credit ratings reduce money left on the table? Evidence from U.S. IPOs - Marc Goergen; Dimitrios Gounopoulos; Panagiotis Koutroumpis (Queen Mary University of London, School of Economics and Finance, 2019)
We examine initial public offerings (IPOs) with single, multiple, and no credit ratings. We document a beneficial effect of credit ratings on IPO underpricing, which is amplified by the existence of multiple credit ratings. Multiple ratings also reduce the extent of filing price revisions. Credit rating levels matter for IPOs with more than one rating but not for those with a single rating. Firms with multiple credit ratings also have higher probabilities of survival than those with a single or no rating. Finally, IPOs awarded a first credit rating between BB and BBB are more likely to seek an additional rating.
Keywords: G10; G14; G39; 330; Initial public offerings (IPOs); credit ratings; IPO underpricing; survivorship